Water Content Analysis and Organoleptic Test on Smoked Catfish In Pasie Pinang Village - Adek Irwanda; Nanda Triandita; Hilka Yuliani (CV. Green Publisher Indonesia, 2022)
Smoking is a method of cooking, flavoring, or preserving food, especially fish meat. The smoking of catfish in Pasie Pinang Village is still done in the traditional way. Smoking is done with coconut fiber, wood and sawdust as fuel, smoked fish is smoked with heat and the smoke from the fuel produces a distinctive taste and aroma in fish products and the color becomes golden and brownish. The purpose of this study was to determine the water content of smoked catfish in Pasie Pinang Village and to determine people's preferences for smoked catfish in Pasie Pinang Village. The panelists used in this research were 35 people consisting of students from the University of Teuku Umar. The results showed that the water content of the three smoked catfish samples varied. Organoleptic test (n=35) in terms of color, taste, aroma, texture and overall, from the three samples tested, the fanelis preferred smoked catfish in sample three. The traditional smoking of smoked fish still has a good value on consumer acceptance.